Influence of animal-, environment-, and management-related factors on grazing behavior and performance of rangeland beef heifers - Continanza, Fatima Guadalupe (New Mexico State University (Estados Unidos), 2020)
Tesis para obtener el grado de Doctor of Philosophy, presentada en la New Mexico State University (Estados Unidos), en noviembre de 2019.